Entrepreneurship, Innovation, and Business Environment Adaptation: Determinants of Culinary SMEs’ Performance in Semarang - Wiweko, Aryoga; Hasya, Afina; Anggara, Adi Wahyu (SAFE-Network, 2025)
SMEs are independent productive enterprises managed by individuals or business entities that are not subsidiaries or branches of larger companies. This study aims to analyze the influence of entrepreneurial orientation, business environment adaptation, and business innovation on business performance through competitive advantage among culinary SMEs in Semarang City. The research involved 120 respondents, consisting of owners and managers of culinary SMEs in Semarang. Data were analyzed using the Structural Equation Modelling (SEM) method with the support of IBM AMOS 22 software. The findings reveal that entrepreneurial orientation, business environment adaptation, and innovation influence business performance through competitive advantage. However, only business environment adaptation has a direct effect on business performance without going through competitive advantage, while the other variables impact business performance only when mediated by competitive advantage. Therefore, MSME owners are advised to strengthen their adaptability, business innovation, and entrepreneurial orientation in order to face market dynamics and competition. For further research, it is highly recommended to expand the study to other MSME sectors or different regions to enrich local business development strategies.